Monetary policy in transition: Essays on monetary policy transmission mechanism in China - Tuuli Koivu (Bank of Finland, 2012)
China's economic development has been exceptionally robust since the end of the 1970s, and the country has already emerged as the second biggest economy in the world. In this study, we seek to illuminate the role of the monetary policy in this successful economic performance and as a part of the extensive economic reforms of the last two decades. The five empirical essays seek to discover which monetary policy tools are the most used and most effective for guiding China's economic development. In addition, we explore which monetary policy transmission channels are functioning and to what extent monetary policy impacts inflation and real economic developments in China. The results indicate that the conduct of monetary policy in China differs substantially from what is typical for an advanced market economy, where an independent central bank often aims to hit an inflation target by simply controlling the target interest rate. First, China's monetary policy toolkit is highly diverse. Besides a collection of administrated interest rates, it contains quantitative policy tools and direct guidelines. Second, China's central bank is not independent in its decision-making. For these reasons, it is exceptionally challenging to measure the monetary policy stance or to distinguish monetary policy from other macroeconomic policies in China's case. This has been taken into account in this study by using a variety of monetary-policy indicators. Our results suggest that China's monetary-policy implementation and its transmission to the real economy still rely heavily on quantitative policy tools and direct guidelines; interest rates play a much smaller role, in terms of both usage and effectiveness. Overall, our findings suggest that the direct link between monetary policy and real economic performance is weak in China. On the other hand, this study clearly shows that monetary policy has played a key role in price developments, which tells us that monetary policy has been an important factor in China's economic success.
URN:NBN:fi:bof-201408071705
Keywords: E50; P30; 330; China; monetary policy; economic growth; inflation; exchange rates; Geldpolitik; Wirtschaftswachstum; Geldpolitische Transmission; Inflationssteuerung; Wechselkurspolitik; Zentralbank; Wirtschaftsreform; China